So the gradient is the negative reciprocal of the question so first you have to rearrange the equation into the form y = mx + c so you get 3y = - 5 x + 11 and then y = -5/3 x + 11/3. Now to find the gradient of the line perpendicular to it you do the negative reciprocal and get 3/5 x so now you have the equation y = 3/5 x + c . Now simply substitute your coordinate into the equation to get -2 = 3/5 x -2 + c and 3/5 x -2 is -1.2 so now you have 2 = -1.2 + c so c is 3.2 so your final equation is y = 3/5 x + 3.2 hope this helps :)